2009
DOI: 10.1007/978-3-642-02256-2_58
|View full text |Cite
|
Sign up to set email alerts
|

A Non-local Approach to Shape from Ambient Shading

Abstract: Abstract. We study the mathematical and numerical aspects of the estimation of the 3-D shape of a Lambertian scene seen under diffuse illumination. This problem is known as "shape from ambient shading" (SFAS), and its solution consists of integrating a strongly non-local and non-linear Integro-Partial Differential Equation (I-PDE). We provide a first analysis of this global I-PDE, whereas previous work had focused on a local version that ignored effects such as occlusion of the light field. We also design an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…ambient) continuous field of illumination was studied by Prados et al [27] who demonstrated that shading under such illumination can be ambiguous. Allowing arbitrary illumination but neglecting occlusions, the most general approach is due to Basri et al [28].…”
Section: Related Workmentioning
confidence: 99%
“…ambient) continuous field of illumination was studied by Prados et al [27] who demonstrated that shading under such illumination can be ambiguous. Allowing arbitrary illumination but neglecting occlusions, the most general approach is due to Basri et al [28].…”
Section: Related Workmentioning
confidence: 99%
“…Prados et al [104] have shown how shading caused by occlusion under perfectly ambient illumination can be used to estimate 3D shape. In this thesis we take a step towards incorporating global illumination effects into the inverse rendering process.…”
Section: Global Shadingmentioning
confidence: 99%
“…Langer and Zucker [70] were the first to study the problem from a computational perspective. More recently, Prados et al [104] showed that the problem is ill-posed under certain conditions (see Figure 5.11) and amounts to the solution of a strongly non-local and non-linear Integro-Partial Differential Equation.…”
Section: Shape From Ambient Occlusionmentioning
confidence: 99%
“…Finally, our work is also related to methods that recover shape from AO [17,21], and our algorithm could potentially be used to generate inputs to such methods.…”
Section: Related Workmentioning
confidence: 99%